Surgical options in early cervical cancer - Rob, Lukas; Robova, Helena; Chmel, Roman; Komar, Matej; Halaska, Michael; Skapa, Petr (International journal of hyperthermia, 2012)
Cancer of the cervix is the second most common cancer in women worldwide and the fourth leading cause of cancer mortality in women. Early cervical cancer stage IB1 includes a broad range of disease from clinically undetectable microinvasive cancer to bulky tumours that infiltrated the entire cervix. This article reviews the literature about risk factors and surgical radicality and fertility-sparing surgery in early cervical cancer. The review evaluates selection criteria, preoperative management and the most frequent surgical procedures used for individually tailored surgery for cervical cancer.
Keywords: Cervix Uteri; Humans; cervix uteri; lidé středního věku; zachování plodnosti; výběr pacientů; Fertility Preservation; Patient Selection; Female; dospělí; fertilita; nádory děložního čípku; lidé; Lymph Node Excision; Adult; ženské pohlaví; Middle Aged; Fertility; hysterektomie; Uterine Cervical Neoplasms; lymfadenektomie; Hysterectomy